2018
DOI: 10.1002/evl3.51
|View full text |Cite
|
Sign up to set email alerts
|

Genetic conflict with a parasitic nematode disrupts the legume–rhizobia mutualism

Abstract: Genetic variation for partner quality in mutualisms is an evolutionary paradox. One possible resolution to this puzzle is that there is a tradeoff between partner quality and other fitness‐related traits. Here, we tested whether susceptibility to parasitism is one such tradeoff in the mutualism between legumes and nitrogen‐fixing bacteria (rhizobia). We performed two greenhouse experiments with the legume Medicago truncatula. In the first, we inoculated each plant with the rhizobia Ensifer meliloti and with on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Two plant signals where the evolutionary consequences of eavesdropping deserve to be explored in more detail are the root exudates plants use to communicate with mutualistic microbes, and floral volatiles. Many signals that plants use to communicate with microbial mutualists are also implicated in pathogenesis (Oldroyd, 2013).Furthermore, the ability to form mycorrhizal and rhizobial mutualisms is associated with susceptibility to parasites (Miller, 1993;Wood et al, 2018), consistent with the hypothesis that parasites rely on some of the same signals as mutualists to locate plant hosts. Second, in a recent review, Caruso and Parachnowitsch (2016) proposed a new eavesdropper on floral volatiles: other plants.…”
Section: Do Eavesdroppers Shape Signal Evolution In Plants and Microbes?mentioning
confidence: 62%
See 1 more Smart Citation
“…Two plant signals where the evolutionary consequences of eavesdropping deserve to be explored in more detail are the root exudates plants use to communicate with mutualistic microbes, and floral volatiles. Many signals that plants use to communicate with microbial mutualists are also implicated in pathogenesis (Oldroyd, 2013).Furthermore, the ability to form mycorrhizal and rhizobial mutualisms is associated with susceptibility to parasites (Miller, 1993;Wood et al, 2018), consistent with the hypothesis that parasites rely on some of the same signals as mutualists to locate plant hosts. Second, in a recent review, Caruso and Parachnowitsch (2016) proposed a new eavesdropper on floral volatiles: other plants.…”
Section: Do Eavesdroppers Shape Signal Evolution In Plants and Microbes?mentioning
confidence: 62%
“…Over longer timescales, coevolutionary arms races between signalers, receivers, and eavesdroppers have been hypothesized to drive signal elaboration, facilitate speciation, and favor the evolution of novel signals (West-Eberhard, 1983;Zuk and Kolluru, 1998;Hoskin and Higgie, 2010). Finally, eavesdroppers may contribute to the maintenance of variation in signals by imposing fitness costs on the individuals that produce the most attractive signals (Strauss and Irwin, 2004;Heath and Stinchcombe, 2014;Wood et al, 2018). In the case of microbes, facultative cheating (eavesdropping) has favored the coexistence of multiple quorum sensing alleles in Bacillus subtilis, a classic case of balancing selection (Pollak et al, 2016).…”
Section: Do Eavesdroppers Shape Signal Evolution In Plants and Microbes?mentioning
confidence: 99%
“…A further question of our study was to explore the interaction of rhizobia and nematodes in the same root system. A previous study found a correlation between the ability of different ecotypes of M. truncatula to form galls and nodules (Wood et al, 2018). This suggests common genetic regulation of both interactions, although the molecular basis for this is not understood.…”
Section: ; Heckmannmentioning
confidence: 91%
“…It was hypothesized that natural hosts (wild species) might have evolved signaling mechanisms to preferentially partner with more mutualistic symbionts and to disadvantage less-cooperative ones (Younginger and Friesen, 2019). Evolutionary models predict that such natural surveillance capability can be disrupted during domestication bottlenecks or breeding process because of: (i) trading-offs between partner quality and agricultural traits as a result of negative trait association or antagonistic gene pleiotropy, such as defense versus symbiosis (Chen et al, 2017;Wood et al, 2018) or (ii) relaxed selection against symbiosis disruption in nitrogen-rich soils owing to a lack of observable fitness costs over disrupted symbiosis (Porter and Sachs, 2020). For example, when plants are grown in high-input agricultural soils, genotypes with reduced symbiosis capability are likely to have higher yields because they can freely get sufficient nitrogen from soil without need to allocate photosynthates to rhizobia for symbiosis development.…”
Section: Effect Of Domestication and Breeding On Partner Choice And Smentioning
confidence: 99%